2012
DOI: 10.1682/jrrd.2010.08.0157
|View full text |Cite
|
Sign up to set email alerts
|

Blast exposure and dual sensory impairment: An evidence review and integrated rehabilitation approach

Abstract: Abstract-Combat exposures to blast can result in both peripheral damage to the ears and eyes and central damage to the auditory and visual processing areas in the brain. The functional effects of the latter include visual, auditory, and cognitive processing difficulties that manifest as deficits in attention, memory, and problem solving-symptoms similar to those seen in individuals with visual and auditory processing disorders. Coexisting damage to the auditory and visual system is referred to as dual sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 94 publications
(121 reference statements)
5
26
0
Order By: Relevance
“…As seen in Tables 3 and 4, participants perceived considerable hearing difficulty, such that their FHQ and SSQ questionnaire scores were more like those of older individuals with hearing impairment * [27], than they were to individuals of equivalent age and normal hearing sensitivity [9,42]. A similar finding was reported in a population of OIF Veterans with blast-related TBI, among whom 11 percent reported hearing difficulties yet had clinically normal hearing [12] and in a survey of VA audiologists that found that 92 percent of audiologists encountered at least one OIF/OEF Veteran a month who had difficulties hearing and yet had normal or almost normal pure tone sensitivity, with 53 percent of audiologists encountering between one and three per month and 39 percent encountering four or more per month [14].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As seen in Tables 3 and 4, participants perceived considerable hearing difficulty, such that their FHQ and SSQ questionnaire scores were more like those of older individuals with hearing impairment * [27], than they were to individuals of equivalent age and normal hearing sensitivity [9,42]. A similar finding was reported in a population of OIF Veterans with blast-related TBI, among whom 11 percent reported hearing difficulties yet had clinically normal hearing [12] and in a survey of VA audiologists that found that 92 percent of audiologists encountered at least one OIF/OEF Veteran a month who had difficulties hearing and yet had normal or almost normal pure tone sensitivity, with 53 percent of audiologists encountering between one and three per month and 39 percent encountering four or more per month [14].…”
Section: Discussionmentioning
confidence: 82%
“…In addition to typical postconcussive symptoms, many blast-exposed Veterans report difficulty understanding speech in noise and problems with auditory memory yet have no measureable peripheral auditory deficits [12][13][14]. Some authors have concluded that these auditory complaints reflect symptoms primarily associated with posttraumatic stress disorder (PTSD) [15], while others suggest they are associated with blastrelated TBI [16], and more specifically, blast-related damage to the central auditory system [11][12][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines that do exist emphasize the individualized nature of the treatment plan and the importance of working with a team of specialists [58][59], which is especially important for Veterans with multiple war-related injuries. A recent survey described by Saunders and Echt found that, although nearly all of the VA audiologists who responded had experiences in which OIF/OEF Veterans with normal audiograms complained of difficulties hearing, there was no clear consensus as to what treatment to offer [65]. Treatment approaches described included hearing aids, remotemicrophone technology, and auditory training.…”
Section: Behavioral Central Auditory Test Results For Patients With Bmentioning
confidence: 99%
“…As described in the section on proposed treatment options, one indication that central auditory dysfunction may be more prevalent than is currently known comes from the survey reported by Saunders and Echt [65]. In the spring of 2009, 220 VA audiologists who subscribe to the VA audiology email list were asked "How often do you encounter OIF/OEF Veterans complaining of hearing difficulties who have normal or almost normal thresholds?"…”
Section: Prevalence Of Central Auditory Dysfunction Among Veteransmentioning
confidence: 99%